EFFECTS OF TRASTUZUMAB ON MYOCARDIAL FUNCTION ON BREAST CANCER PATIENTS (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the effect of Trastuzumab on myocardial function on breast cancer patients at Thong Nhat hospital. Subjects and methods: a retrospective study on 48 patients with breast cancer treated with Trastuzumab at Thong Nhat hospital. Results: Percentage of patients with heart failure according to the Frammingham diagnostic criteria was 4.17%. The proportion of patients with no symptoms of heart failure according to Frammingham diagnostic criteria was 95.83%. According to the degree of EF change, the proportion of patients with decreased EF > 10% after treatment was 43.75%. With 9 patients with EF < 53%, accounting for 18.75%. The proportion of patients who had to discontinue therapy due to cardiotoxicity during treatment with Trastuzumab was 12.5%, with 6.25% stopping completely and 6.25% of patients stopping temporarily. Conclusion: the rate of patients with heart failure was little, the proportion of EF
Keywords: Breast cancer, myocardial function, Trastuzumab